Healthcare practitioners and students' PEP knowledge, attitude and adherence in Southern Africa - Lufuno Makhado; Ofhani P. Musekwa; Thendo G. Makhado; Reamogetse Otsheleng (AOSIS, 2022)
Background: There is a high prevalence of occupational exposure among health care practitioners (HCPs) around the globe. One of the risk factors of HIV infection among HCPs is occupational exposure to human immunodeficiency virus (HIV) infection through blood or fluid from HIV-infected individual. Therefore, because of this prevalence, there is a need to have sufficient knowledge and information regarding post-exposure prophylaxis (PEP). Sufficient PEP knowledge assists individuals in utilising PEP in case of exposure to HIV. Aim: This study aims to assess the level of knowledge, attitude and adherence to PEP in HCPs in Southern Africa. Setting: The systematic review included studies conducted in Southern Africa. Methods: A systematic review was conducted. Search engines employed in this study included Google Scholar, Science Direct, PubMed, Ebscohost and JSTOR. From these, 3572 articles emerged after removing duplications, and article screening was guided by inclusion and exclusion criteria and outlined on a PRISMA flow chart. Ultimately, the study included 13 articles. A critical appraisal skills programme was applied for the quality assessment of the eligible studies. Results: Studies included in this review revealed that most participants have adequate knowledge regarding PEP (n = 6). However, it was revealed that poor adherence occured because most HCPs did not complete PEP. Conclusion: Health care practitioners have adequate knowledge of PEP with varying levels of adherence to PEP. Therefore, more awareness illustrating the importance of adhering to PEP is needed. Contribution: There is an adequate level of knowledge regarding PEP found in the included studies although not satisfactory in Southern Africa given the participants are HCPs, and marked inappropriate practices affect adherence.